Pengaruh Promosi dan Kemudahan Penggunaan Terhadap Kepuasan Nasabah dalam Bertransaksi Menggunakan Layanan Livin By Mandiri pada PT. Bank Mandiri di Kota Banjarmasin - Nirwandani; Setio Utomo; Rizki Muslim Hidayat (Smart Business Journal (SBJ), 2022)
This studies is a quantitative studies, this kind of studies is associative. Sampling on this observe used the Accidental Sampling technique, as a way to reap sixty five respondents who have been used as studies samples. The information used have been taken from a questionnaire. Data evaluation used more than one linear regression evaluation.The outcomes display that X1 (Promotion) has a sig cost of 0.000, because of this that it's miles smaller than 0.05, then Ho is rejected. Ha is generic, that means that Promotion has a huge impact on Customer Satisfaction. X2 (Ease of Use) has a sig cost of 0.one hundred and five because, because of this that it's miles extra than 0.05, then Ho is generic, Ha is rejected, that means that Ease of Use has no huge impact on Customer Satisfaction. And the sig cost withinside the F check is 0.000 because of this that much less than 0.05, then Ho is rejected and Ha is generic because of this that Promotion (X1), and Ease of Use (X2) simultaneously (together) has a huge impact on Customer Satisfaction (Y) .So, the conclusions on this observe are: (1) Promotion in part has a huge impact on Customer Satisfaction, (2) Partial Ease of Use has no huge impact on Customer Satisfaction, and (3) Promotion, and Simultaneous Ease of Use have a huge impact on Customer Satisfaction